1999
DOI: 10.1210/en.140.11.5364
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Effects of Neonatal Estrogen Exposure in Rats on Reproductive Hormone Levels, Sertoli Cell Number, and the Efficiency of Spermatogenesis in Adulthood

Abstract: This study aimed to identify the mechanism(s) for impairment of spermatogenesis in adulthood in rats treated neonatally with estrogens. Rats were treated (days 2-12) with 10, 1, or 0.1 microg diethylstilbestrol (DES), 10 microg ethinyl estradiol (EE), 10 mg/kg of a GnRH antagonist (GnRHa), or vehicle and killed in adulthood. DES/EE caused dose-dependent reductions in testis weight, total germ cell volume per testis, and Sertoli cell volume per testis. Sertoli cell number at 18 days of age in DES-treated rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
151
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(162 citation statements)
references
References 0 publications
7
151
0
4
Order By: Relevance
“…It is interesting to note that these two studies were the only ones to assess the effects of life-long exposure (from conception to adulthood). In addition, both studies reported a decrease in litter size (21-40%), whereas the other three studies evaluating litter size effects at precise windows of exposure found no effects (Atanassova et al, 1999;Nagao et al, 2001;Tan et al, 2006). These findings suggest that negative effects on sperm production and male fertility in rodents are only observed during a life-long exposure to soy and phytoestrogens.…”
Section: Soy Phytoestrogens and Male Reproductive Functionmentioning
confidence: 80%
“…It is interesting to note that these two studies were the only ones to assess the effects of life-long exposure (from conception to adulthood). In addition, both studies reported a decrease in litter size (21-40%), whereas the other three studies evaluating litter size effects at precise windows of exposure found no effects (Atanassova et al, 1999;Nagao et al, 2001;Tan et al, 2006). These findings suggest that negative effects on sperm production and male fertility in rodents are only observed during a life-long exposure to soy and phytoestrogens.…”
Section: Soy Phytoestrogens and Male Reproductive Functionmentioning
confidence: 80%
“…Previous studies have demonstrated that high doses of potent estrogens, such as DES, are clearly inhibitory to testicular development over both the short and long term [3,25]. The results of the present histological analyses in the groups exposed to DES neonatally showed a thinning of germ cell layers in the seminiferous tubules, which suggests a reduction of spermatogenesis, and the hypoplasia of the Leydig cells and epididymal ducts of the cauda epididymis at 8 weeks of age; however, the groups exposed to DES in utero but not treated neonatally showed no histological changes in the testis or epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, long-term changes, including molecular alterations, have been observed after exposure to endocrine disrupting chemicals during these early developmental periods [13,28]. In addition, it has been reported that neonatal exposure of animals to estrogenic compounds caused disorders of the male reproductive tract [24], reduction of testosterone [3], testicular atrophy and carcinoma [17,21], increased rate of breast cancer [8], uterine adenocarcinoma and various cervicovaginal lesions [18,20]. Diethylstilbestrol (DES), a synthetic non-steroidal estrogen, exhibits a high estrogenic activity by binding to the ERs, and is thus a useful model compound for evaluating the potential toxicity of a wide range of chemicals that affect or mimic estrogen activity [7].…”
mentioning
confidence: 99%
“…Se sabe que la exposición prenatal o neonatal de fetos machos a altas concentraciones de estradiol resulta en una disminución del número de células de Sertoli, deficiencia de la espermatogénesis y aumento de la apoptosis (dependiente de la concentración) en la etapa adulta 21 . El uso de dietiletilbestrol en la prevención del parto prematuro, se encontró claramente asociado a un aumento de cáncer testicular, criptorquidia e hipospadia en los hijos varones de las mujeres tratadas 22,23 .…”
Section: Reprogramación Fetalunclassified